Concomitant Use of Proton Pump Inhibitors With Capecitabine Based Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer: Is it Safe?. (September 2021) - Menon, Anjali; Abraham, Aswin G.; Mahfouz, Maria; Thachuthara, Joseph J.; Usmani, Nawaid; Warkentin, Heather; Ghosh, Sunita; Nijjar, Tirath; Severin, Diane; Tankel, Keith; Paulson, Kim; Mulder, Karen; et al.
Abstract : Aim: Capecitabine (Cape) is routinely used for the neoadjuvant chemoradiation treatment (NACRT) of locally advanced rectal cancers (LARCs). Previous reports have suggested that the concomitant use of proton pump inhibitors (PPIs) may affect the efficacy of Cape, although the true effect of PPIs when used with Cape as a radiosensitizer for neoadjuvant radiation is unclear. The aim of our study was to evaluate the impact of concurrent PPI use along with fluorouracil (FU) and Cape based NACRT in terms of pathologic and oncological outcomes, in patients with LARC. Methods: LARC patients treated at our center with NACRT from 2010 to 2016 were identified. Postoperative pathology and follow-up outcomes were examined for any differences with relation to the use of PPIs concurrently with FU and Cape based NACRT and adjuvant chemotherapy regimens. Results: Three hundred four and 204 patients received treatment with FU and Cape based NACRT. No difference in pathologic complete response rate was noted between the 2 arms with the concurrent use of PPIs (25.8% and 25%, respectively, P =0.633); or with and without the use of PPIs in the Cape-NACRT arm specifically (20% and 20.7%, P =0.945). At a median follow-up of 5 years, no statistical difference in local or distant control was noted in the Cape-NACRT patients, with and without concomitant PPI use ( P =0.411 and 0.264, respectively). Multivariate analysis showed no association of PPI use and NACRT with Cape, in terms of local control (hazard ratio=0.001, P =0.988) or overall survival (hazard ratio=1.179, confidence interval=0.249-5.579, P =0.835). Conclusions: Our study revealed that there was no adverse pathologic or oncological outcome with the concurrent use of PPIs along with Cape-NACRT in the treatment of LARC. We report that it may be safe to use PPIs if essential, in this clinical setting, although it would be wise to exercise caution. Abstract : Supplemental Digital Content is available in the text.